A Comprehensive Update of the Incidence and Demographics of Laryngoceles in Adults. (October 2022) - Slonimsky, Einat; Goldenberg, David; Hwang, Gloria; Gagnon, Eric; Slonimsky, Guy
Objective: To provide updated data on the incidence, types, and demographics of laryngoceles in the adult population. Methods: We searched the medical archives of our institute for computed tomography (CT) studies acquired between January 1, 2007 and December 31, 2017 in which the term "laryngocele" appeared in the radiology reports. Two of the authors reviewed relevant images for the presence, type, distribution, and laterality of true laryngoceles. Demographic and clinical data were extracted from medical records and the incidence was calculated. Results: Laryngoceles were detected in 53 out of the 79 893 patients with relevant CT data, which equates to an incidence of 151 per 2.5 million (0.06:1000) patients per year. The male:female ratio was 3:1, average age was 60 (±18) years, and incidence peaked among patients in the sixth decade of life. Nine patients (17%) had known laryngeal cancer; however, the majority of the cohort did not have follow up clinic visits. Conclusion: Our study demonstrates that the incidence of laryngoceles is much greater than previously reported. In most cases, the diagnosis of a laryngocele was an incidental radiological finding. Male gender predilection and age at presentation are in agreement with previous reports. Association of laryngoceles with laryngeal cancer could not be calculated due to low rates of follow ups. Level of Evidence: 3.